Asymmetric α-electrophilic difluoromethylation of β-keto esters by phase transfer catalysis. Issue 21 (13th May 2021) - Wang, Yakun; Wang, Shuaifei; Qiu, Peiyong; Fang, Lizhen; Wang, Ke; Zhang, Yawei; Zhang, Conghui; Zhao, Ting
Abstract : Enantioselective electrophilic difluoromethylation by phase transfer catalysis. Abstract : An efficient and enantioselective α-electrophilic difluoromethylation of β-keto esters has been achieved by phase-transfer catalysis. This procedure is applicable to different kinds of β-keto esters with a series of cinchona-derived C-2′ aryl-substituted phase-transfer catalysts. The reaction gives the corresponding products in good enantioselectivities (up to 83% ee) and yields (up to 92%) with high C/O regioselectivities (up to 98 : 2). Moreover, the C/O selectivity of β-keto esters could be easily reversed and controlled. This asymmetric difluoromethylation provided a novel and efficient way for introducing chiral C-CF2 H groups.